Caribbean economic handbook - Fraser, Peter D. (Euromonitor Publications LondonGB, 1985)
Provides an economic analysis and overview of the Caribbean including Cuba, Haiti, Bermuda, the Bahamas, and the Cayman Islands. Explores existing differences in the region as well as common problems. Examines the region's role in and relationship to the rest of the world and discusses its prospects for the future. Gives in-depth analysis of the major countries of the region. Contains a fact file of statistics on individual territories in the region.